A porous catalyst carrier and a method for producing the same
Patent Information
- Application Number
- CN202611285746.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-16
AI Technical Summary
现有硅铝锆稀土复合载体制备工艺多采用金属前驱体一锅共混溶胶凝胶方法,存在诸多难以解决的技术问题:其一,金属盐一次性混合水解容易造成局部离子过饱和,易生成氢氧化物团聚沉淀,难以在硅氧骨架表面形成均匀键合界面,造成金属掺杂组分分散不均,载体水热稳定性差、高温下易发生骨架致密化与晶粒粗化;其二,传统工艺多采用单一配体络合稀土离子,仅能实现基础的稀土离子稳定的目的,稀土组分在凝胶干燥及高温焙烧过程中易发生迁移、团聚与相偏析,难以形成均匀弥散的稀土活性固溶相,氧空位数量少且分布不均,载体界面催化调控能力受限
本发明提供了一种多孔催化剂载体及其制备方法,该制备方法包括:先将九水硝酸铝与硝酸氧锆混合,制得金属盐溶液,再滴加至酸性硅溶胶中,全程调控pH并恒温老化,得到掺杂硅溶胶;将六水硝酸铈、六水硝酸钇混合,制得稀土盐溶液,依次加入无水柠檬酸、甘氨酸、葡萄糖酸,构建三元梯度配位体系,调节pH使反应充分,制得稳定性良好的螯合溶液;然后将螯合溶液滴加至掺杂硅溶胶中,经凝胶成型、梯度干燥、破碎筛分、分段焙烧、冷却,最终制得多孔催化剂载体。本发明使用稀的金属盐溶液缓慢滴加并结合滴加过程中pH调控、恒温老化工艺,可避免氢氧化物沉淀生成,提供充足时间促进金属水合离子与硅羟基脱水缩合,在纳米SiO2颗粒表面形成Si-O-Al、Si-O-Zr杂化键修饰层,构建表面异质成核位点,获得水热稳定性高且均匀的掺杂硅溶胶。掺杂硅溶胶与螯合溶液之间的相容性好,可为后续借助掺杂位点诱导稀土组分原位异相成核提供基础。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst support technology, and specifically to a porous catalyst support and its preparation method. Background Technology
[0002] Porous silicon-based catalyst supports are widely used in catalysis. The sol-gel method is one of the mainstream processes for preparing multi-component composite porous silicon-based catalyst supports due to its good component doping uniformity and strong pore structure tunability. Existing silicon-aluminum-zirconium rare earth composite support preparation processes mostly adopt the one-pot sol-gel method of metal precursor mixing, which has many difficult technical problems to solve: First, the one-time mixing and hydrolysis of metal salts can easily cause local ion supersaturation, easily generating hydroxide agglomerates and precipitates, making it difficult to form a uniform bonding interface on the silicon-oxygen framework surface, resulting in uneven dispersion of metal dopants, poor hydrothermal stability of the support, and easy densification and grain coarsening of the framework at high temperatures; Second, traditional processes mostly use single ligands to complex rare earth ions, which can only achieve the basic purpose of rare earth ion stabilization. Rare earth components are prone to migration, agglomeration and phase segregation during gel drying and high-temperature calcination, making it difficult to form a uniformly dispersed rare earth active solid solution phase. The number of oxygen vacancies is small and unevenly distributed, limiting the catalytic regulation ability of the support interface.
[0003] In addition, conventional sol-gel systems have a simple pore-forming mechanism and concentrated pyrolysis zones of organic additives. During calcination, a large amount of gas is easily generated instantaneously, which leads to stress collapse of the gel pore walls and an increase in closed and defective pores. The resulting catalyst supports have problems such as wide pore size distribution, poor pore connectivity, and low pore volume utilization, which seriously restricts the mass transfer efficiency between reactants and products.
[0004] Therefore, developing a high-performance porous composite catalyst support is of great engineering application value, as it addresses the shortcomings of existing technologies such as uneven dispersion of doped components, easy agglomeration of rare earth components, poor controllability of pore structure, and weak interfacial synergistic effect. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a porous catalyst support and its preparation method.
[0006] The objective of this invention can be achieved through the following technical solutions: A method for preparing a porous catalyst support includes the following steps: Step S1: Add aluminum nitrate nonahydrate and zirconium oxynitrate to deionized water and stir until homogeneous to obtain a metal salt solution; stir the acidic silica sol and then add the metal salt solution dropwise, adjusting the pH during the dropwise addition; after the dropwise addition is complete, heat and continue stirring, then cool to obtain a doped silica sol. Step S2: Add cerium nitrate hexahydrate and yttrium nitrate hexahydrate to deionized water and stir until homogeneous to obtain a rare earth salt solution. Add anhydrous citric acid to the rare earth salt solution, heat and stir, then add glycine and continue stirring. Add gluconic acid and continue stirring. Adjust the pH and continue stirring to obtain a chelated solution. Step S3: Add the chelation solution dropwise to the doped silica sol, adjusting the pH during the dropwise addition. After the dropwise addition is complete, heat and stir, then cool and let stand to obtain a gel system. Dry the gel system, crush and sieve it, calcine it, and cool it to obtain a porous catalyst support.
[0007] A method for preparing a porous catalyst support includes the following specific steps: Step S1: Add aluminum nitrate nonahydrate and zirconium oxynitrate to deionized water and stir for 10-15 min to obtain a metal salt solution; control the stirring speed at 400-500 rpm and stir the acidic silica sol for 20-25 min, then add the metal salt solution dropwise over 1-1.5 h. During the dropwise addition, use 5% ammonia and 0.5 mol / L nitric acid solution to adjust the pH to 3.2-4.2 bidirectionally. After the dropwise addition is complete, heat to 40-50℃ and continue stirring for 2.5-3.5 h. Cool to obtain the doped silica sol. Furthermore, the molar ratio of aluminum nitrate nonahydrate to zirconium oxynitrate is 0.8-1.2:1; the ratio of the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate to the volume of deionized water is 1 mol: 3.5-4.5 L.
[0008] Furthermore, based on the total molar amount of silicon in the acidic silica sol, the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate accounts for 5-8% of the total molar amount of silicon in the acidic silica sol.
[0009] Step S2: Add cerium nitrate hexahydrate and yttrium nitrate hexahydrate to deionized water and stir for 10-15 min to obtain a rare earth salt solution. Add anhydrous citric acid to the rare earth salt solution, heat to 43-45℃, stir for 30-35 min, then add glycine and continue stirring for 30-35 min. Add gluconic acid and continue stirring for 30-35 min. Adjust the pH to 4.2-4.6 with 5% ammonia water and continue stirring for 1-1.2 h to obtain a chelated solution. Furthermore, the molar ratio of cerium nitrate hexahydrate to yttrium nitrate hexahydrate is 7-7.2:3-3.2; the ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate to the volume of deionized water is 1 mol:4.0-5.0 L.
[0010] Furthermore, the molar ratio of the total molar amounts of cerium nitrate hexahydrate and yttrium nitrate hexahydrate, anhydrous citric acid, glycine, and gluconic acid is 1:0.7-1.0:0.4-0.7:0.3-0.6.
[0011] Step S3: Under a stirring speed of 450-550 rpm, the chelation solution is added dropwise to the doped silica sol over a period of 1.1-1.3 h. During the addition, the pH is adjusted to 3.2-4.4 using 0.5 mol / L nitric acid solution. After the addition is complete, the mixture is heated to 40-44℃ and stirred for 2-3 h. Then it is cooled and allowed to stand for 16-17 h to obtain a gel system. The gel system is dried, crushed through a 60-80 sieve, calcined, and cooled to obtain a porous catalyst support.
[0012] Furthermore, the volume ratio of the chelating solution to the doped silica sol is 0.45-0.65:1.
[0013] Furthermore, the drying process is as follows: dry at 60℃ for 8-10 hours, then heat to 80℃ for 12-13 hours, and then heat to 110℃ for 12-13 hours.
[0014] Furthermore, the calcination process is as follows: first, the temperature is increased to 260℃ at a rate of 2℃ / min and held for 1-1.2h; then, the temperature is increased to 420℃ at a rate of 2℃ / min and held for 1.5-1.7h; finally, the temperature is increased to 580℃ at a rate of 2℃ / min and held for 3-3.2h.
[0015] A porous catalyst support prepared by the above-mentioned method.
[0016] The beneficial effects of this invention are: This invention provides a porous catalyst support and its preparation method. The preparation method includes: first, mixing aluminum nitrate nonahydrate and zirconium oxynitrate to obtain a metal salt solution, then adding it dropwise to an acidic silica sol, adjusting the pH throughout the process and aging at a constant temperature to obtain a doped silica sol; mixing cerium nitrate hexahydrate and yttrium nitrate hexahydrate to obtain a rare earth salt solution, then sequentially adding anhydrous citric acid, glycine, and gluconic acid to construct a ternary gradient coordination system, adjusting the pH to ensure a complete reaction, and obtaining a chelated solution with good stability; then adding the chelated solution dropwise to the doped silica sol, followed by gel forming, gradient drying, crushing and sieving, segmented calcination, and cooling to finally obtain a porous catalyst support. This invention utilizes a slow, dropwise addition of a dilute metal salt solution, combined with pH control and isothermal aging during the addition process. This avoids the formation of hydroxide precipitation and provides sufficient time to promote the dehydration condensation of hydrated metal ions and silanol groups, forming a Si-O-Al and Si-O-Zr hybrid bond modification layer on the surface of nano-SiO2 particles. This constructs heterogeneous nucleation sites on the surface, resulting in a highly hydrothermally stable and uniform doped silica sol. The good compatibility between the doped silica sol and the chelation solution provides a foundation for subsequent in-situ heterogeneous nucleation of rare earth components induced by the doping sites.
[0017] This invention utilizes a ternary ligand of citric acid, glycine, and gluconate to synergistically complex cerium and yttrium ions. Citric acid, with its polycarboxyl groups, strongly coordinates with cerium and yttrium ions, serving as the main chelating agent to stabilize rare earth ions. Glycine has moderate coordination strength, which can appropriately regulate the dissociation equilibrium of the chelate. Gluconate relies on its flexible polyhydroxy long chain to construct spatial barriers through hydrogen bonds. The ternary ligands exhibit a gradient distribution of coordination strength, with overlapping and progressively advancing thermal decomposition zones, continuously inhibiting the migration and aggregation of rare earth components during calcination.
[0018] This invention involves dropwise incorporating a chelating solution into a doped silica sol, inducing heterogeneous nucleation of rare-earth oxides through Si-O-Al and Si-O-Zr doping sites to construct multiple compact heterogeneous interfaces. During calcination, specific proportions of cerium and yttrium components form a fluorite-structured solid solution, enhancing electron transfer and oxygen vacancy regulation. During calcination, glycine preferentially decomposes at 220-320℃ to create pores, citric acid decomposes at 280-400℃ to increase pore volume, and gluconic acid continuously and slowly generates gas at 380-500℃ to prevent pore collapse, ultimately yielding a porous catalyst support with better connectivity and a narrower pore size distribution. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1 A method for preparing a porous catalyst support includes the following steps: Step S1: Add aluminum nitrate nonahydrate and zirconium oxynitrate to deionized water and stir for 10 min at room temperature to obtain a metal salt solution. Control the stirring speed at 400 rpm and stir the acidic silica sol (supplier: Heyuan Sodium Silicate Factory, Duruan Town, Pengjiang District, Jiangmen City, effective ingredient content: 30%) at room temperature for 20 min. Then add the metal salt solution dropwise over 1 hour. During the dropwise addition, adjust the pH to 3.2 using 5% ammonia and 0.5 mol / L nitric acid solution. After the dropwise addition is complete, heat to 40°C and continue stirring for 2.5 hours. Allow to cool naturally to room temperature to obtain a doped silica sol. The molar ratio of aluminum nitrate nonahydrate to zirconium oxynitrate is 0.8:1. The ratio of the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate to the volume of deionized water is 1 mol: 3.5 L. Based on the total molar amount of silicon in the acidic silica sol, the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate accounts for 5% of the total molar amount of silicon in the acidic silica sol.
[0021] Step S2: Add cerium nitrate hexahydrate and yttrium nitrate hexahydrate to deionized water and stir at room temperature for 10 min to obtain a rare earth salt solution. Add anhydrous citric acid to the rare earth salt solution, heat to 43°C, and stir for 30 min. Then add glycine and continue stirring at 43°C for 30 min. Add gluconic acid and continue stirring at 43°C for 30 min. Adjust the pH to 4.2 with 5% ammonia water and continue stirring at 43°C for 1 h to obtain a chelated solution. The molar ratio of cerium nitrate hexahydrate to yttrium nitrate hexahydrate is 7:3. The ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate and the volume of deionized water is 1 mol: 4.0 L. The molar ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate, anhydrous citric acid, glycine, and gluconic acid is 1:0.7:0.4:0.3.
[0022] Step S3: At room temperature and with a stirring speed of 450 rpm, the chelating solution was added dropwise to the doped silica sol over 1.1 h. During the addition, the pH was adjusted to 3.2 using 0.5 mol / L nitric acid solution. After the addition was complete, the mixture was heated to 40 °C and stirred for 2 h, then cooled to room temperature and allowed to stand for 16 h to obtain a gel system. The gel system was dried, crushed through a 60-sieve, calcined, and naturally cooled to room temperature to obtain a porous catalyst support. The volume ratio of the chelating solution to the doped silica sol was 0.45:1. The drying process was as follows: drying at 60 °C for 8 h, then heating to 80 °C for 12 h, and then heating to 110 °C for 12 h. The calcination process was as follows: first, the temperature was increased to 260 °C at a rate of 2 °C / min and held for 1 h, then increased to 420 °C at a rate of 2 °C / min and held for 1.5 h, and finally increased to 580 °C at a rate of 2 °C / min and held for 3 h.
[0023] Example 2 A method for preparing a porous catalyst support includes the following steps: Step S1: Add aluminum nitrate nonahydrate and zirconium oxynitrate to deionized water and stir for 13 min at room temperature to obtain a metal salt solution. Control the stirring speed at 450 rpm and stir the acidic silica sol (supplier: Heyuan Sodium Silicate Factory, Duruan Town, Pengjiang District, Jiangmen City, effective ingredient content: 35%) at room temperature for 23 min. Then add the metal salt solution dropwise over 1.3 h. During the dropwise addition, the pH is controlled at 3.7 by bidirectional adjustment using 5% ammonia water and 0.5 mol / L nitric acid solution. After the dropwise addition is complete, heat to 45℃ and continue stirring for 3.0 h. Allow to cool naturally to room temperature to obtain a doped silica sol. The molar ratio of aluminum nitrate nonahydrate to zirconium oxynitrate is 1.0:1. The ratio of the total molar amount of aluminum nitrate nonahydrate to zirconium oxynitrate to the volume of deionized water is 1 mol: 4.0 L. Based on the total molar amount of silicon in the acidic silica sol, the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate accounts for 6.5% of the total molar amount of silicon in the acidic silica sol.
[0024] Step S2: Add cerium nitrate hexahydrate and yttrium nitrate hexahydrate to deionized water and stir at room temperature for 13 min to obtain a rare earth salt solution. Add anhydrous citric acid to the rare earth salt solution, heat to 44℃, and stir for 33 min. Then add glycine and continue stirring at 44℃ for 33 min. Add gluconic acid and continue stirring at 44℃ for 33 min. Adjust the pH to 4.4 with 5% ammonia water and continue stirring at 44℃ for 1.1 h to obtain a chelated solution. The molar ratio of cerium nitrate hexahydrate to yttrium nitrate hexahydrate is 7.1:3.1. The ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate and the volume of deionized water is 1 mol:4.5 L. The molar ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate, anhydrous citric acid, glycine, and gluconic acid is 1:0.8:0.5:0.4.
[0025] Step S3: At room temperature and with a stirring speed of 500 rpm, the chelating solution was added dropwise to the doped silica sol over 1.2 h. During the addition, the pH was adjusted to 3.8 using 0.5 mol / L nitric acid solution. After the addition was complete, the mixture was heated to 42 °C and stirred for 2.5 h. Then, it was cooled to room temperature and allowed to stand for 16.5 h to obtain a gel system. The gel system was dried, crushed through a 70-sieve, calcined, and naturally cooled to room temperature to obtain a porous catalyst support. The volume ratio of the chelating solution to the doped silica sol was 0.55:1. The drying process was as follows: drying at 60 °C for 9 h, then heating to 80 °C for 12.5 h, and then heating to 110 °C for 12.5 h. The calcination process was as follows: first, the temperature was increased to 260 °C at a rate of 2 °C / min and held for 1.1 h, then increased to 420 °C at a rate of 2 °C / min and held for 1.6 h, and finally increased to 580 °C at a rate of 2 °C / min and held for 3.1 h.
[0026] Example 3 A method for preparing a porous catalyst support includes the following steps: Step S1: Add aluminum nitrate nonahydrate and zirconium oxynitrate to deionized water and stir for 15 min at room temperature to obtain a metal salt solution. Control the stirring speed at 500 rpm and stir the acidic silica sol (supplier: Heyuan Sodium Silicate Factory, Duruan Town, Pengjiang District, Jiangmen City, effective ingredient content: 40%) at room temperature for 25 min. Then add the metal salt solution dropwise over 1.5 h. During the dropwise addition, the pH is controlled at 4.2 by bidirectional adjustment using 5% ammonia water and 0.5 mol / L nitric acid solution. After the dropwise addition is complete, heat to 50℃ and continue stirring for 3.5 h. Allow to cool naturally to room temperature to obtain a doped silica sol. The molar ratio of aluminum nitrate nonahydrate to zirconium oxynitrate is 1.2:1. The ratio of the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate to the volume of deionized water is 1 mol: 4.5 L. Based on the total molar amount of silicon in the acidic silica sol, the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate accounts for 8% of the total molar amount of silicon in the acidic silica sol.
[0027] Step S2: Add cerium nitrate hexahydrate and yttrium nitrate hexahydrate to deionized water and stir at room temperature for 15 min to obtain a rare earth salt solution. Add anhydrous citric acid to the rare earth salt solution, heat to 45°C, and stir for 35 min. Then add glycine and continue stirring at 45°C for 35 min. Add gluconic acid and continue stirring at 45°C for 35 min. Adjust the pH to 4.6 with 5% ammonia water and continue stirring at 45°C for 1.2 h to obtain a chelated solution. The molar ratio of cerium nitrate hexahydrate to yttrium nitrate hexahydrate is 7.2:3.2. The ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate and the volume of deionized water is 1 mol:5.0 L. The molar ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate, anhydrous citric acid, glycine, and gluconic acid is 1:1.0:0.7:0.6.
[0028] Step S3: At room temperature and with a stirring speed of 550 rpm, the chelating solution was added dropwise to the doped silica sol over 1.3 h. During the addition, the pH was adjusted to 4.4 using 0.5 mol / L nitric acid solution. After the addition was complete, the mixture was heated to 44 °C and stirred for 3 h. Then, it was cooled to room temperature and allowed to stand for 17 h to obtain a gel system. The gel system was dried, crushed and passed through an 80-sieve, calcined, and naturally cooled to room temperature to obtain a porous catalyst support. The volume ratio of the chelating solution to the doped silica sol was 0.65:1. The drying process was as follows: drying at 60 °C for 10 h, then heating to 80 °C for 13 h, and then heating to 110 °C for 13 h. The calcination process was as follows: first, the temperature was increased to 260 °C at a rate of 2 °C / min and held for 1.2 h, then increased to 420 °C at a rate of 2 °C / min and held for 1.7 h, and finally increased to 580 °C at a rate of 2 °C / min and held for 3.2 h.
[0029] Comparative Example 1 Compared with Example 3, gluconic acid was not used, and the total molar amounts of cerium nitrate hexahydrate and yttrium nitrate hexahydrate, the molar ratio of anhydrous citric acid and glycine were 1:1.3:1.0. The rest was exactly the same as in Example 3, and a porous catalyst support was prepared.
[0030] Comparative Example 2 Compared with Example 3, glycine was not used, the total molar amounts of cerium nitrate hexahydrate and yttrium nitrate hexahydrate, the molar ratio of anhydrous citric acid and gluconic acid were 1:1.35:0.95, and the rest were exactly the same as in Example 3, thus preparing a porous catalyst support.
[0031] Comparative Example 3 Compared with Example 3, anhydrous citric acid was not used, the total molar amounts of cerium nitrate hexahydrate and yttrium nitrate hexahydrate, the molar ratio of glycine and gluconic acid were 1:1.2:1.1, and the rest were exactly the same as in Example 3, thus preparing a porous catalyst support.
[0032] Comparative Example 4 Compared with Example 3, instead of preparing the doped silica sol and chelation solution step by step, the metal salt solution and rare earth salt solution are directly added to the acidic silica sol in sequence, and then mixed with anhydrous citric acid, glycine and gluconic acid to obtain gel system-1. Gel system-1 is used to replace gel system, and the rest is exactly the same as in Example 3 to prepare a porous catalyst support. Specifically: Aluminum nitrate nonahydrate and zirconium oxynitrate were added to deionized water and stirred at room temperature for 15 min to obtain a metal salt solution. Cerium nitrate hexahydrate and yttrium nitrate hexahydrate were added to deionized water and stirred at room temperature for 15 min to obtain a rare earth salt solution. Acidic silica sol (supplier: Heyuan Sodium Silicate Factory, Duruan Town, Pengjiang District, Jiangmen City, effective ingredient content: 40%) was stirred at room temperature for 25 min, and the metal salt solution and rare earth salt solution were added dropwise sequentially. The metal salt solution and rare earth salt solution were added together over 1.5 h. During the addition, the solution was adjusted bidirectionally using 5% ammonia water and 0.5 mol / L nitric acid solution. The pH was adjusted to 4.2. After the addition was complete, the mixture was heated to 50°C and stirred for 3.5 h. After cooling naturally to room temperature, anhydrous citric acid was added, and the mixture was heated to 45°C and stirred for 35 min. Glycine was then added, and the mixture was stirred at 45°C for 35 min. Glucosic acid was added, and the mixture was stirred at 45°C for 35 min. The pH was adjusted to 4.4 using 0.5 mol / L nitric acid solution. After the addition was complete, the mixture was stirred at 45°C for 3 h. After cooling to room temperature, the mixture was allowed to stand for 17 h to obtain gel system-1. Gel system-1 was dried, crushed and passed through an 80-sieve, calcined, and then cooled naturally to room temperature to obtain a porous catalyst support. The molar ratio of aluminum nitrate nonahydrate to zirconium oxynitrate is 1.2:1; the ratio of the total molar amount of aluminum nitrate nonahydrate to zirconium oxynitrate to the volume of deionized water is 1 mol: 4.5 L; the molar ratio of cerium nitrate hexahydrate to yttrium nitrate hexahydrate is 7.2:3.2; the ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate to the volume of deionized water is 1 mol: 5.0 L; based on the total molar amount of silicon in the acidic silica sol, the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate accounts for 8% of the total molar amount of silicon in the acidic silica sol; the total molar amount of cerium nitrate nonahydrate to zirconium oxynitrate accounts for 8% of the total molar amount of silicon in the acidic silica sol; the total molar amount of cerium nitrate hexahydrate to zirconium oxynitrate is 1 mol: 1; the total molar amount of cerium nitrate nonahydrate to zirconium oxynitrate is 1 mol: 4.5 L; the total molar amount of cerium nitrate hexa ... The total molar amounts of cerium nitrate and yttrium nitrate hexahydrate, anhydrous citric acid, glycine, and gluconic acid were in the molar ratio of 1:1.0:0.7:0.6. The drying process was as follows: drying at 60℃ for 10 hours, then heating to 80℃ for 13 hours, and then heating to 110℃ for 13 hours. The calcination process was as follows: first heating to 260℃ at a rate of 2℃ / min and holding for 1.2 hours, then heating to 420℃ at a rate of 2℃ / min and holding for 1.7 hours, and finally heating to 580℃ at a rate of 2℃ / min and holding for 3.2 hours.
[0033] Comparative Example 5 Compared with Example 3, the doped silica sol in step S3 was replaced by an equal mass of acidic silica sol in step S1, while the rest was exactly the same as in Example 3, to prepare a porous catalyst support.
[0034] Comparative Example 6 Compared with Example 3, the chelating solution in step S3 was replaced by an equal mass of the rare earth salt solution in step S2, while the rest was exactly the same as in Example 3, to prepare a porous catalyst support.
[0035] Comparative Example 7 Compared with Example 3, the order of adding anhydrous citric acid and gluconic acid in step S2 was changed, while the rest was exactly the same as in Example 3, to prepare a porous catalyst support. Specifically: Step S2: Add cerium nitrate hexahydrate and yttrium nitrate hexahydrate to deionized water and stir at room temperature for 15 min to obtain a rare earth salt solution. Add gluconic acid to the rare earth salt solution, heat to 45°C, and stir for 35 min. Then add glycine and continue stirring at 45°C for 35 min. Add anhydrous citric acid and continue stirring at 45°C for 35 min. Adjust the pH to 4.6 with 5% ammonia water and continue stirring at 45°C for 1.2 h to obtain a chelated solution. The molar ratio of cerium nitrate hexahydrate to yttrium nitrate hexahydrate is 7.2:3.2. The ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate and the volume of deionized water is 1 mol:5.0 L. The molar ratio of the total molar amount of cerium nitrate hexahydrate to yttrium nitrate hexahydrate, anhydrous citric acid, glycine, and gluconic acid is 1:1.0:0.7:0.6.
[0036] The porous catalyst supports prepared in Examples 1-3 and Comparative Examples 1-7 of this invention were further tested below, and the results are shown in the figure.
[0037] The 77K low-temperature nitrogen adsorption-desorption method was used for testing. Before the test, the porous catalyst support was placed in a vacuum at 200℃ for 4 hours for degassing. The specific surface area was calculated using the BET model, and the total pore volume, average pore size, and pore size distribution curve were calculated using the BJH adsorption branch. The half-maximum width of the pore size distribution was obtained by Gaussian fitting of the pore size distribution curve, which was used to evaluate the uniformity of the pore size distribution.
[0038] The porous catalyst support was placed in a tube furnace and heated to 700°C at a rate of 3°C / min in an air atmosphere (flow rate of 40 mL / min). After aging for 20 h and naturally cooling to room temperature, the specific surface area after high-temperature aging was tested to evaluate high-temperature stability.
[0039] The porous catalyst support was placed in a tubular reactor for hydrothermal aging. The volume fraction of water vapor in the air was 10%. The temperature was increased to 600℃ at a rate of 2℃ / min and aged for 10h. After natural cooling to room temperature, the specific surface area after hydrothermal aging was tested to evaluate the hydrothermal aging resistance.
[0040] The results are recorded in Table 1.
[0041] Table 1: Performance test results of porous catalyst supports According to the data in Table 1, the porous catalyst supports prepared in Examples 1-3 of the present invention have good specific surface area, total pore volume, high temperature stability and hydrothermal stability, and the average pore size is moderate. The half-peak width of the pore size distribution curve is small, indicating that the pore size distribution is narrow and the pore structure is uniform.
[0042] Compared with Comparative Example 1, Example 3 shows that Comparative Example 1 lacks the spatial barrier formed by gluconic acid; the roasting process lacks the continuous and slow gas production and pore formation in the later stage, the pore walls are prone to shrinkage, the number of closed pores increases, the degree of rare earth component aggregation increases, the specific surface area and total pore volume of the obtained porous catalyst support decreases, the half-peak width of the pore size distribution curve increases, the pore size uniformity deteriorates, and both high-temperature stability and hydrothermal stability decrease.
[0043] Compared with Comparative Example 2, Example 3 shows that Comparative Example 2 lacks the moderate strength ligand of glycine to regulate the chelation balance. During the drying and calcination stages, rare earth components migrate slightly, the distribution pore-forming timing matching degree decreases, the specific surface area and total pore volume of the obtained porous catalyst support decrease, the half-width of the pore size distribution curve increases, the pore size uniformity deteriorates, and both high-temperature stability and hydrothermal stability decrease.
[0044] Comparing Example 3 with Comparative Example 3, it can be seen that Comparative Example 3 lacks anhydrous citric acid as the main strong chelating agent, which makes it impossible to form a stable chelating framework for rare earth ions. The stability of rare earth components decreases. At the same time, due to the lack of the stepwise pore-forming effect of citric acid at medium temperature, the pore support effect during the calcination process is severely insufficient, and the pore collapse is obvious. The specific surface area and total pore volume of the obtained porous catalyst support are greatly reduced, the pore size distribution is significantly widened, the rare earth components are severely aggregated, the solid solution structure is difficult to form, and the high temperature stability and hydrothermal stability of the catalyst support are significantly deteriorated.
[0045] Comparing Example 3 with Comparative Example 4, it can be seen that Comparative Example 4 did not use ternary organic ligands to grade rare earths for hierarchical chelation, but directly used rare earth salt solutions. No coordination chelates were formed, and the rare earth components were not sterically constrained, making them prone to self-phase aggregation. The phenomenon of pore collapse during the calcination process increased, resulting in a decrease in the specific surface area and total pore volume of the obtained porous catalyst support. The half-width of the pore size distribution curve increased, the pore size uniformity deteriorated, and both high-temperature stability and hydrothermal stability decreased.
[0046] Comparing Example 3 with Comparative Example 5, it can be seen that Comparative Example 5 introduces aluminum salt and zirconium oxynitrate for framework doping, lacks Si-O-Al and Si-O-Zr modification layers, rare earth components agglomerate on the surface, have weak interfacial bonding with silica, are prone to sintering at high temperatures, the specific surface area and total pore volume of the obtained porous catalyst support decrease, the half-width of the pore size distribution curve increases, the pore size uniformity deteriorates, and both high-temperature stability and hydrothermal stability decrease.
[0047] Comparing Example 3 with Comparative Example 6, it can be seen that in Comparative Example 6, free rare earth ions are easily hydrolyzed and aggregated upon contact with acidic silica sol, forming large particles of rare earth hydroxide, which block the pores in large quantities. As a result, the specific surface area and total pore volume of the obtained porous catalyst support are reduced significantly, the half-peak width of the pore size distribution curve increases significantly, the pore size uniformity deteriorates significantly, and the high-temperature stability and hydrothermal stability decrease significantly.
[0048] Comparing Example 3 with Comparative Example 7, it can be seen that in Comparative Example 7, the order of adding citric acid and gluconic acid was changed, the dispersion of rare earth components became worse, the synergistic effect of stepwise pore formation by ligands during the roasting stage was weakened, and the pores collapsed; the specific surface area and total pore volume of the resulting catalyst support decreased, the average pore size increased, the half-peak width of the pore size distribution differential curve increased significantly, the pore size uniformity deteriorated, and the high-temperature stability and hydrothermal stability decreased.
[0049] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a porous catalyst support, characterized in that: Includes the following steps: Step S1: Add aluminum nitrate nonahydrate and zirconium oxynitrate to deionized water and stir until homogeneous to obtain a metal salt solution; stir the acidic silica sol and then add the metal salt solution dropwise, adjusting the pH during the dropwise addition; after the dropwise addition is complete, heat and continue stirring, then cool to obtain a doped silica sol. Step S2: Add cerium nitrate hexahydrate and yttrium nitrate hexahydrate to deionized water and stir until homogeneous to obtain a rare earth salt solution. Add anhydrous citric acid to the rare earth salt solution, heat and stir, then add glycine and continue stirring. Add gluconic acid and continue stirring. Adjust the pH and continue stirring to obtain a chelated solution. Step S3: Add the chelation solution dropwise to the doped silica sol, adjusting the pH during the dropwise addition. After the dropwise addition is complete, heat and stir, then cool and let stand to obtain a gel system. Dry the gel system, crush and sieve it, calcine it, and cool it to obtain a porous catalyst support.
2. The method for preparing a porous catalyst support according to claim 1, characterized in that: In step S1, the molar ratio of aluminum nitrate nonahydrate to zirconium oxynitrate is 0.8-1.2:1; the ratio of the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate to the volume of deionized water is 1 mol: 3.5-4.5 L.
3. The method for preparing a porous catalyst support according to claim 1, characterized in that: In step S1, the total molar amount of silicon in the acidic silica sol is used as a basis, and the total molar amount of aluminum nitrate nonahydrate and zirconium oxynitrate accounts for 5-8% of the total molar amount of silicon in the acidic silica sol.
4. The method for preparing a porous catalyst support according to claim 1, characterized in that: In step S2, the molar ratio of cerium nitrate hexahydrate to yttrium nitrate hexahydrate is 7-7.2:3-3.
2.
5. The method for preparing a porous catalyst support according to claim 1, characterized in that: In step S2, the ratio of the total molar amount of cerium nitrate hexahydrate and yttrium nitrate hexahydrate to the volume of deionized water is 1 mol: 4.0-5.0 L.
6. The method for preparing a porous catalyst support according to claim 1, characterized in that: In step S2, the molar ratio of the total molar amounts of cerium nitrate hexahydrate and yttrium nitrate hexahydrate, anhydrous citric acid, glycine, and gluconic acid is 1:0.7-1.0:0.4-0.7:0.3-0.
6.
7. The method for preparing a porous catalyst support according to claim 1, characterized in that: In step S3, the volume ratio of the chelating solution to the doped silica sol is 0.45-0.65:
1.
8. The method for preparing a porous catalyst support according to claim 1, characterized in that: In step S3, the drying process is as follows: drying at 60°C for 8-10 hours, then heating to 80°C for 12-13 hours, and then heating to 110°C for 12-13 hours.
9. The method for preparing a porous catalyst support according to claim 1, characterized in that: In step S3, the calcination process is as follows: first, the temperature is increased to 260℃ at a rate of 2℃ / min and held for 1-1.2h; then, the temperature is increased to 420℃ at a rate of 2℃ / min and held for 1.5-1.7h; finally, the temperature is increased to 580℃ at a rate of 2℃ / min and held for 3-3.2h.
10. A porous catalyst support prepared by the method of any one of claims 1-9.